Validity of Ultrasonography for the Estimation of Macrosomia among Pregnant women with Diabetes Mellitus (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Estimation of fetal weight by ultrasonography is crucial for the determination of macrosomia cases among the pregnant women with diabetes mellitus.Objectives: The purpose for the present study was to validate the ultrasonography for the estimation of fetal weight among the macrosomia cases in pregnant women with diabetes mellitus.Methodology: This cross-sectional study was carried out in inpatient Department of Obstetrics and Gynecology and in outpatients Department of Radiology and Imaging, Bangladesh Institute of Research and Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) at Dhaka, Bangladesh during the period of April 2005 to March 2007. Pregnant women with diagnosed DM or GDM selected for caesarean section or induction of labour, gestational age 236 weeks having 23700 gm by clinical method were included in this study. First clinical estimation of fetal weight was done by the investigator then Radiologist estimated the fetal weight without knowing the EFW by clinical method. The actual birth weight was estimated after the birth of the babies.Result: It was found that in 56.5% and 60.9% cases was evaluated as macrosomia in clinical and USG examination respectively (p>0.05). Clinically and actually macrosomia were found 56.5% and 63.8% respectively (p>0.05). It was found that in 60.9% cases macrosomia at USG diagnosis and 63.8% case was macrosomia actually (p>0.05). It was observed that out of 39 macrosomia cases evaluated clinically could ultimately evaluate 27(69.2%) cases after birth, USG detected 42 macrosomia which ultimately evaluate 30(71.4%) cases, and actually after birth macrosomia found 44(63.8%). The validity of clinical and sonographic method for evaluation of macrosomia were studied by sensitivity, specificity and accuracy which were 61.4%, 52.0%, 58.0% and 68.2%, 52.0%, 62.3% respectively.Conclusion: In conclusion the ultrasonography is poor diagnostic tools for the estimation of macrosomia among the diabetic mother.Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 40-44